The impact of Servant Leadership on Organizational Trust: The Mediating Role of Organizational Culture - Bader Ali Almutairi; Mohammad Abd-alkarim Alraggad; Mohammad Khasawneh (European Scientific Journal, ESJ, 2020)
This study aims to examine the impact of servant leadership on organizational trust and mediating role of organizational culture for the mentioned relationship for employees in the Kuwaiti Ministry of Higher Education. A survey questionnaire was used as the main instrument for data collection. A total of 285 questionnaires were distributed among the Kuwaiti Ministry of Higher Education employees. In total, 248 valid questionnaires to analysis were returned equivalent to 87% response rate. Data analysis was conducted with the help of PLS-SEM to determine the level of relationships among servant leadership, organizational trust, and organizational culture. According to the obtained findings, there is a positive impact of servant leadership on organizational trust, and organizational culture has a partially mediated role in the relationship between servant leadership and organizational trust. The study findings motivate future studies to carry out studies of the same caliber in other sectors to obtain different perspectives.